2018
DOI: 10.1371/journal.pone.0200899
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient-specific computational models vs. clinical follow-up, for adjacent segment disc degeneration and bone remodelling after spinal fusion

Abstract: Spinal fusion is a standard surgical treatment for patients suffering from low back pain attributed to disc degeneration. However, results are somewhat variable and unpredictable. With fusion the kinematic behaviour of the spine is altered. Fusion and/or stabilizing implants carrying considerable load and prevent rotation of the fused segments. Associated with these changes, a risk for accelerated disc degeneration at the adjacent levels to fusion has been demonstrated. However, there is yet no method to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
0
33
0
Order By: Relevance
“…Strain energy density calculations in the AF further considered the anisotropy induced by the oriented collagen type I. Composition-dependent tissue modeling has paved the way to map the relative effects of local ECM depletion, in the NP, the AF, and the CEP, on the biphasic behavior of the IVD and on the indirect mechanotransduction phenomena [ 37 , 68 ]. Such tissue models were also coupled to phenomenological direct mechanotransduction theories, initially developed to predict the fate of bone MSC in endochondral bone healing, to calculate the likely long-term IVD remodeling after spine surgery [ 449 ]. The effect of PG and fixed-charge density contents on the diffusion of antibiotics from the vasculature to the IVD was also assessed through finite element mechano-transport simulations [ 450 , 451 ].…”
Section: Systems’ Modeling For the Exploration Of Ivd Degenerativementioning
confidence: 99%
“…Strain energy density calculations in the AF further considered the anisotropy induced by the oriented collagen type I. Composition-dependent tissue modeling has paved the way to map the relative effects of local ECM depletion, in the NP, the AF, and the CEP, on the biphasic behavior of the IVD and on the indirect mechanotransduction phenomena [ 37 , 68 ]. Such tissue models were also coupled to phenomenological direct mechanotransduction theories, initially developed to predict the fate of bone MSC in endochondral bone healing, to calculate the likely long-term IVD remodeling after spine surgery [ 449 ]. The effect of PG and fixed-charge density contents on the diffusion of antibiotics from the vasculature to the IVD was also assessed through finite element mechano-transport simulations [ 450 , 451 ].…”
Section: Systems’ Modeling For the Exploration Of Ivd Degenerativementioning
confidence: 99%
“…2 Spinal fusion provided by rigid stabilization has been considered as the gold standard for the operation of DDD; 3,4 however, it was observed that it could lead to the adjacent segment disease (ASD). 5,6 General causes of the ASD are attributed to the increased motion and changing the instantaneous centre of rotation. 7 The clinical reports regarding that the ASD can be occurred in the range of 12.2%–35% after fusion operation.…”
Section: Introductionmentioning
confidence: 99%
“…It originated from the EU-funded MySpine project (EU FP7-ICT 269909) that included lower back pain patients and was approved by the Scientific Research Ethics Committee of the Medical Research Council (751/PI/2010) of the National Center for Spinal Disorders, Budapest, Hungary. Details of the patients and models can be found elsewhere and are only summarized here [11,12]. Computed tomography (CT) and magnetic resonance imaging (MRI) scans were used to segment the vertebrae and intervertebral discs (IVDs), respectively [13,14].…”
Section: Fe Models Of the Intact Lumbar Spinementioning
confidence: 99%
“…Although it is premature to interpret the exact quantity of the tissue volume at risk, the relative changes between different situations and load-steps indicate a relative risk of that particular configuration. To get a more extensive validation of the tissue being at risk, we need to implement nonlinear material behavior for the bone, including elastic-plasticdamage behavior, and to implement a tissue degeneration model for the disc [12]. This would involve the introduction of many new parameters and require further experimental validation of the model which is outside the scope of this publication.…”
Section: Vertebraementioning
confidence: 99%